Topographic anatomy of the lateral surface of the parietal lobe and its relationship with white matter tracts - Oğlin, Volkan; Orhun, Ömer; Quiñones-Hinojosa, Alfredo; Middlebrooks, Erik H.; Çevik, Orhun Mete; Usseli, M. İmre and Güdük, Mustafa and Aksoy, M. Emin and Pamir, M. Necmettin and Bozkurt, Baran (Frontiers in Neuroanatomy, 2024)
Aim of the study to define sulcal and gyral variations of the lateral parietal cortex and underlying white matter tracts and emphasize the importance of relationship between topographic anatomy of parietal lobe and white matter tracts underlying it in approaches to deep parietal and atrial lesions. Twenty-eight formalin-fixed cerebral hemispheres of 14 adult cadavers were used. Ten hemispheres were dissected from lateral to medial by fiber dissection technique and all stages were photographed. Our anatomic findings were supported by MRI tractography. Postcentral sulcus and intraparietal sulcus were continuous in most of the cadavers (71% in right, 64% in left side). Intermediate sulcus of Jensen was in bayonet shape in 86 and 50 percent of cadavers at right and left side, respectively. The range of perpendicular distance between the meeting point and interhemispheric fissure was 2.5 -4.9 cm in right and 2.8 -4.2 cm in left hemisphere whereas the range of distance between meeting point and the sylvian fissure was 3 -6 cm and 2.5 -5.6 in left and right hemispheres, respectively. When the meeting point was located more laterally, the probability of damaging the arcuate fasciculus and superior longitudinal fasciculus II during dissection was increased. We also found that the intraparietal sulcus and intermediate sulcus of Jensen were associated with the superior longitudinal fasciculus II, middle longitudinal fasciculus, inferior frontooccipital fasciculus, tapetum, and optic radiation. These variations and their relation to subcortical tracts should be considered in atrium and deep parietal lobe surgeries.